Radiotherapy for keratoacanthoma of facial skin: A case report and review of literature - Jia, Xiaojing; Ge, Ying; Wang, Hongyong; Ma, Yan (Frontiers in Oncology, 2023)
Background: Keratoacanthoma (KA) is a benign tumor originating from the infundibulum of the hair follicle, but some scholars believe that KA belongs to a subtype of squamous cell carcinoma (SCC), or belongs to the borderline benign and malignant tumor. KA is divided into single-type and multiple-type. Surgical resection is the first choice for the treatment of KA. For patients with large lesions who are not suitable for surgery, the treatment options are limited. Here，we reports a case of single-type KA with large lesions that was not suitable for surgery, and the lesions basically disappeared after radiotherapy. No recurrence was found during the two-year follow-up. Case Description: A 62-year-old male patient was admitted to the dermatology department of our hospital in June 2020 due to the discovery of a red papule on the right face 2 months ago, with occasional itching, which gradually increased. The diagnosis of KA was confirmed by pathological examination. Due to the large lesions and underlying diseases, he was transferred to our radiotherapy department for radiotherapy after consultation. At the end of radiotherapy, the patient's facial tumor was dry and subsided. Two years after radiotherapy, the facial tumor subsided significantly, and the damaged skin on the face basically recovered to a flat shape. Conclusions: Radiotherapy is a safe and effective treatment for patients with large lesions of single-type KA.